Peningkatan Literasi Kesehatan dan Kesejahteraan Ibu Hamil melalui Edukasi Terintegrasi dan Praktik Yoga Prenatal - Maria Goreti Benga; Ida Sofiyanti; Syarifah Zaidah Putri Al-Hinduan (Universitas Ngudi Waluyo, 2025)
The second and third trimesters of pregnancy are often accompanied by physical discomforts such as back pain and anxiety before childbirth. Prenatal yoga is an effective non-pharmacological intervention to improve physical fitness and mental balance for pregnant women. This community service activity aims to increase knowledge as well as the physical and mental readiness of pregnant women through education and prenatal yoga stimulation. The activity was carried out simultaneously in two locations: Klinik Pratama Polda Kaltara (Tarakan) and TPMB Eka Putri (Tanjung Selor) in December 2025. The targets were 10 pregnant women in their second and third trimesters. The methods included theoretical education, video tutorial demonstrations, and prenatal yoga practice (Warrior poses and relaxation). The evaluation was measured using pre-test and post-test instruments and testimonial interviews. The analysis showed a significant increase in knowledge; before the intervention, the majority of participants (80%) were in the